PKM KELOMPOK TANI RAWANG BELENGAI: PEMANFAATAN JAKABA SEBAGAI BIOREMEDIATOR DALAM PEMBUATAN POP DAN POC UNTUK MENDUKUNG PERTANIAN RAMAH LINGKUNGAN - Sari, Dia Novita; Togatorop, Eny Rolenti Togatorop; Novita Hamron; Parwito, Parwito (Fakultas Pertanian, 2025)
The soaring price of fertilizer followed by the scarcity of fertilizer supplies has caused farmers to be unable to buy. The impact of this has caused crop production to decline and has decreased farmers' income. This community service activity aims to provide a solution to reduce fertilizer prices by introducing and practicing how to make solid organic fertilizer (SOF) and liquid organic fertilizer (LOF). The community service activity method uses socialization, practice, application of technology, assistance, and evaluation. The perceptions and expectations before and after the practice of making solid organic fertilizer and liquid organic fertilizer are the same, namely 95% are in the high category. All participants were very enthusiastic about the solid organic fertilizer and liquid organic fertilizer manufacturing technology package, as seen from the high perception of 95%. Participants also have high expectations of 95% for the technology package provided as seen that the participants will practice making SOF and LOF independently.